Combination of TWEAK and TGF-β1 induces the production of TSLP, RANTES, and TARC in BEAS-2B human bronchial epithelial cells during epithelial-mesenchymal transition. (9th August 2018) - Matsuno, Kei; Harada, Norihiro; Harada, Sonoko; Takeshige, Tomohito; Ishimori, Ayako; Itoigawa, Yukinari; Katsura, Yoko; Kodama, Yuzo; Makino, Fumihiko; Ito, Jun; Atsuta, Ryo; Akiba, Hisaya; et al.
Abstract: Aim of the study : In patients with asthma, chronic inflammatory processes and the subsequent remodeling of the airways contribute to the symptoms and the pathophysiological changes. Epithelial-mesenchymal transition (EMT) is thought to play an important role in tissue remodeling. Previous reports show that tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) is a cytokine of the TNF superfamily, exerts pro-inflammatory effects, and enhances transforming growth factor (TGF)-β-induced EMT in bronchial epithelial cells. In this study, we investigated the TWEAK-induced cytokine and chemokine production in the human bronchial epithelial cell line BEAS-2B during EMT.Materials and Methods : Quantitative real-time RT-PCR, enzyme-linked immunosorbent assays, western blotting, and immunohistochemistry were used to define the production of cytokines and chemokines.Results : We found that TWEAK increases mRNA and protein levels of thymic stromal lymphopoietin (TSLP), monocyte chemoattractant protein -1 (MCP-1), regulated upon activation normal T cell express sequence (RANTES), and IL-8 in BEAS-2B bronchial epithelial cells. Moreover, co-treatment with TWEAK and TGF-β1 induces not only features of EMT but also enhances the production of TSLP and RANTES. Thymus- and activation-regulated chemokines (TARC) production is induced by the co-treatment of TWEAK and TGF-β1 but not by TWEAK or TGF-β1 stimulation alone. Furthermore, the increased mRNA expression of TSLP and RANTES after co-treatment with TWEAK and TGF-β1 is prevented by inhibitors of Smad-independent signaling pathways.Conclusions : In the present study, we have revealed a novel mechanism for the production of asthma-related cytokines and chemokines in EMT driven by the co-stimulation with TWEAK and TGF-β1. We conclude that cellular EMT processes caused by TWEAK and TGF-β1 may contribute to chronic airway inflammation and remodeling.